Dialogues between children of childhood education and a teacher around the work Cena de rua (Street scene), by Angela Lago - Arena, Dagoberto Buim [UNESP]; Santos, Sonia de Oliveira [UNESP] (Univ Federal Espirito Santo, 2020)
This article is the result of research carried out around the Street Scene Book, by Angela Lago. The objective is to understand the dialogues between children aged 4 and 5 and a teacher at a public early childhood school in Marilia (Sao Paulo) while reading the work. The guiding questions were: What knowledge and experience do Brazilian children insert in the dialogues? What are the common or distinct aspects, highlighted by them, from their cultural reference universe? What are the referrals made by the teacher? The theoretical framework for the analysis of the dialogues is in accordance with the conceptions of language by Valentin Volochinov (2002; 2010) and Lev Jakubinskij (2012). The results indicate that children interpret works of art from the social, economic and cultural place in which they find themselves and according to their psychic formation based on their experiences.
Keywords: Early Childhood Education; Reading; Children's Literature; Street Scene Book